Deep neck abscesses: study of 101 cases - Brito,Thiago Pires (2017)
Abstract Introduction: Although the incidence of Deep Cervical Abscess (DCA) has decreased mainly for the availability of antibiotics, this infection still occurs with considerable frequency and can be associated with high morbidity and mortality. Objective: This study aimed to present our clinical-surgical experience with deep neck abscesses. Methods: A retrospective study analyzed 101 patients diagnosed with deep neck abscesses caused by multiple etiologies, assisted at a medical school hospital during 6 years. One hundred one patients were included and 27 (26.7%) were younger than 18 years old (the children group), 74 patients (73.3%) were older than 18 years old (the adults group). The following clinical features were analyzed and compared: age, gender, clinical symptoms, leukocyte count, the affected cervical area, lifestyle habits, antibiotic therapy, comorbidities, etiology, bacterial culture, time of hospitalization, the need of tracheostomy and complications. Results: There was predominance in the male gender (55.5%) and young people (mean age 28.1 years). All of the 51 patients with associated disease comorbidity were adults. The most frequent etiologies were bacterial tonsillitis (31.68%) and odontogenic infections (23.7%). The most common cervical areas affected were the peritonsillar (26.7%), submandibular/mouth floor (22.7%) and parapharyngeal spaces (18.8%). In children group, the site most commonly involved was the peritonsillar space (10 patients, 37%). In adults group, the site most commonly involved was multispace (31 patients, 41.8%). Streptococcus pyogenes (23.3%) was the most common microorganism present. Amoxicillin associated with clavulanate (82.1%) was the more used antibiotic. The main complications of abscesses were septic shock (16.8%), pneumonia (10.8%) and mediastinitis (1.98%). Tracheostomy was necessary in 16.8% of patients. The mortality rate was 1.98%. Conclusion: The clinical features and severity of DCA varied according to different age groups, perhaps due to the location of the infection and a higher incidence of comorbidity in adults. Thus, DCA in adults is more facile to have multispace involvement and lead to complications and seems to be more serious than that in children.